Unique elements of Polish city brands in online reviews - Nowacki, Marek (Turyzm/Tourism, 2019)
The aim of the paper is to identify unique elements of the brands of Polish cities and to identify similarities and differences between them. The work attempts to answer the following research questions: Which elements significantly differentiate the brands of studied cities in online reviews? and Which of the studied cities are the most similar in terms of brand elements and which differ in this regard. The data for analysis was obtained from TripAdvisor. Reviews about areas of tourist concentration – old markets or old towns – from five Polish cities: Poznań, Wrocław, Kraków, Gdańsk and Warsaw were analysed (N = 5125). The research shows that Gdańsk and Warsaw as well as Poznań and Wrocław have the most similar brand elements. The Kraków brand is the more unique in relation to other cities.